2020
DOI: 10.7717/peerj.8811
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of CONUT score combined with serum CA199 levels in postoperative survival of patients with pancreatic ductal adenocarcinoma: a retrospective study

Abstract: Background The preoperative controlling nutritional status (CONUT) score and serum carbohydrate antigen 199 (CA199) levels are individually correlated with the prognosis of pancreatic ductal adenocarcinoma (PDAC). The objective of this study aimed to investigate the efficacy of CONUT score and CA199 (CONUT-CA199) combination in predicting the prognosis of PDAC patients undergoing radical surgery. Methods We retrospectively analyzed the preoperative CONUT scores and serum CA199 levels of 294 patients with PDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Among them, the neutrophil lymphocyte ratio (NLR) and prognostic nutritional index (PNI) were considered to be independent prognostic factors that affect the survival of many malignancies (20)(21)(22)(23), and the Controlled Nutritional Status (CONUT) score, as an immune nutritional status scoring system that emerged in 2005, also took serum cholesterol into account when assessing the immune nutritional status of patients compared to PNI and NLR (24,25). The CONUT score, which is comprised of the serum values of albumin (ALB), total lymphocyte count (TLC), and total cholesterol, is considered to be a prognostic factor for postoperative prognosis of malignant tumors such as carcinoma of colon, non-small cell lung cancer, liver cancer and pancreatic ductal adenocarcinoma (26)(27)(28)(29), and has also been reported to be an important prognostic factor for survival in nonresectable HCCA (30).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the neutrophil lymphocyte ratio (NLR) and prognostic nutritional index (PNI) were considered to be independent prognostic factors that affect the survival of many malignancies (20)(21)(22)(23), and the Controlled Nutritional Status (CONUT) score, as an immune nutritional status scoring system that emerged in 2005, also took serum cholesterol into account when assessing the immune nutritional status of patients compared to PNI and NLR (24,25). The CONUT score, which is comprised of the serum values of albumin (ALB), total lymphocyte count (TLC), and total cholesterol, is considered to be a prognostic factor for postoperative prognosis of malignant tumors such as carcinoma of colon, non-small cell lung cancer, liver cancer and pancreatic ductal adenocarcinoma (26)(27)(28)(29), and has also been reported to be an important prognostic factor for survival in nonresectable HCCA (30).…”
Section: Introductionmentioning
confidence: 99%
“…The baseline characteristics of the seven included studies are presented in Table 2 . Four studies were conducted in Japan ( 9 , 10 , 13 , 16 ), and three were performed in China ( 12 , 14 , 15 ). The sample size ranged from 72 to 589, with a median of 307.…”
Section: Resultsmentioning
confidence: 99%
“…The sample size ranged from 72 to 589, with a median of 307. Six studies were retrospective ( 9 , 10 , 12 14 , 16 ), and one was prospective ( 15 ). All studies included patients with pancreatic ductal adenocarcinoma (PDAC).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have identified that CA19-9 is a reliable and validated indicator for predicting prognosis of patients with pancreatic cancer (23,24). Also, Wang et al (25) proved that serum CA19-9 levels may act as an independent factor to predict postoperative survival of patients with PDAC. Therefore, CA19-9 which is included in our model could increase specificity and sensitivity of the nomogram.…”
Section: Discussionmentioning
confidence: 98%